New Tools, Old Goals: Comparing the Role of Technology in the 1979 Iranian Revolution and The 2009 Green Movement - Rahaghi, John A. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: What role does technology play in a mass uprising or revolution? Can it aid in fomenting mass protests? In the 1979 Iranian Revolution, the technology of the day - cassette tapes and photocopied pamphlets - were credited with helping faciliate the revolution. In 2009, modern communication tools such as the Internet and mobile phones were present in Iran, but the uprising was not successful. By comparing the two events, it becomes clear that one has to understand the opposition: its goals, structure, organization, leadership, and the political context involved, before determining the role of technology. Once a movement is defined, the specific use of technology for recruiting, motivating, organizing, and informing the outside world can be understood. Technology is not inherently revolutionary in and of itself, and is dependent on the users if it is to achieve the lofty attributes some ascribe to it.